Art Organisers as Commoners: On the Sustainability and Counter‐Hegemonic Potential of the Bangkok Biennial - Wissink, Bart (2022)
As part of a remarkable wave of perennial contemporary art events in Thailand, the Bangkok Biennial was organised for the first time in 2018. Without central curation or funding, the organisational strategy of this artist‐led, open‐access event was strikingly different from the state‐organised Thailand Biennale and the corporate Bangkok Art Biennale that were inaugurated several months later. Through the eyes of the literature on “commoning” as a third way of organising next to the state and market, we explore the “common spaces” that the Bangkok Biennial has produced. Reflecting on arguments articulated in the introduction to this thematic issue, as well as on Chantal Mouffe’s analysis of the detrimental nature of an “exodus strategy” for counter‐hegemonic action, we focus on the connections—if any—of the Bangkok Biennial with the state and corporations. Specifically, we address the following research questions: What are the characteristics of the Bangkok Biennial as a common art event? Which connections with the state and market have its organisers developed? And what are the consequences of this strategy for its sustainability and counter‐hegemonic potential? We conclude that the organisers have consciously resisted developing relationships with the state and market, and argue that this “exodus strategy” is a necessity in Thailand’s socio‐political setting. And while this strategy might endanger the sustainability of this biennial as an art event, we argue that at the same time it supports an infrastructure for counter‐hegemonic action inside and—possibly more importantly—outside art.